Synthesis and Characterization of 2D Metal-Organic Frameworks for Adsorption of Carbon Dioxide and Hydrogen - Tshuma, Piwai; Makhubela, Banothile C. E.; Ndamyabera, Christophe A.; Bourne, Susan A.; Mehlana, Gift (Frontiers in Chemistry, 2020)
The reaction of Cd(NO3)2·4H2O and Zn(NO3)2·6H2O with the bipyridyl ligand H2bpdc (2,2’-bipyridine-4,4’-dicarboxylic acid) afforded two porous metal organic frameworks [Cd(bpdc)2(DMF)2·2DMF]n (JMS-3) and [Zn(bpdc)(DMF)·DMF]n (JMS-4). Single crystal X-ray diffraction analysis reveal that JMS-3 crystallizes in the monoclinic crystal system and space group P21/c, whereas JMS-4 crystallizes in the monoclinic system and space group P21. The MOFs possess 2D interdigited networks with (sql) topology. Sorption studies showed that the activated phase of JMS-3 had CO2 volumetric uptakes of 26.50 and 30.89 cm3 (STP) g-1 (1.18 and 1.39 mmolg-1) whist JMS-4 gave 10.96 and 16.08 cm3 (STP) g-1 (0.49 and 0.71 mmolg-1) at 298 and 273 K respectively.